2012
DOI: 10.1017/s0317167100015365
|View full text |Cite
|
Sign up to set email alerts
|

The Haplotype of the TGFβ1 Gene Associated with Cerebral Infarction in Chinese

Abstract: Background:Transforming growth factor beta1 (TGFβ1) is a multifunctional cytokine involved in inflammation and pathogenesis of atherosclerosis. The aim of the present study was to investigate the relationship between human TGFβ1 gene +869T>C (rs1800470), -509C>T (rs1800469) single nucleotide polymorphisms (SNPs) and haplotypes and cerebral infarction (CI) in a Chinese population.Methods:The genetic association study was performed in 450 Chinese patients (306 male and 144 female) with CI and 450 control s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
0
12
2
Order By: Relevance
“…Different to our results, intercellular adhesion molecule 1 rs5498 was found to be associated with ischaemic stroke risk in Caucasians but not in Asians in a meta-analysis [5]. In contrast to some previous studies and in line with the results presented here, a recent meta-analysis did not detect a significantly in-creased risk of stroke in carriers of ILA rs1894399 and CD14 rs2569190 [19]. The rare allele of TNF rs1800629 was protective against stroke in Asian, but not in Caucasian populations according to a recent meta-analysis [16], in line with the neutral result in our population.…”
Section: Comparison With Previous Studiescontrasting
confidence: 86%
See 1 more Smart Citation
“…Different to our results, intercellular adhesion molecule 1 rs5498 was found to be associated with ischaemic stroke risk in Caucasians but not in Asians in a meta-analysis [5]. In contrast to some previous studies and in line with the results presented here, a recent meta-analysis did not detect a significantly in-creased risk of stroke in carriers of ILA rs1894399 and CD14 rs2569190 [19]. The rare allele of TNF rs1800629 was protective against stroke in Asian, but not in Caucasian populations according to a recent meta-analysis [16], in line with the neutral result in our population.…”
Section: Comparison With Previous Studiescontrasting
confidence: 86%
“…Non-inflammatory genes and genes without reported association with above vascular diseases were not considered. The following variants were selected: IL1A rs1894399 [11], IL1B rs16944 [12], IL1RN rs380092 [12], IL6 pro-inflammatory haplotype [13], IL6 receptor (IL6R) rs2228145 [14], IL10 rs1800872 [15], tumour necrosis factor-a (TNF) rs1800629 [16], C-C motif che-DOI: 10.1159/000507042 mokine ligand 2 rs1024611 [17], CCR5 rs333 [17], CRP pro-inflammatory haplotype [18], intercellular adhesion molecule 1 rs5498 [5], TGFB1 rs1800469 [19], E-Selectin rs5361 [20], SEPS rs9874 [21], cluster determinant (CD) 14 rs2569190 [22,23] and HDAC9 rs11984041 [24]. Haplotype analysis was performed for CRP (3 SNPs) and IL6 (6 SNPs).…”
Section: Extended Gene Scorementioning
confidence: 99%
“…Till date, a few studies have been published on the association between TGF-β1 polymorphisms[23242526272829] and risk of IS with one SNP and only two studies have examined the TGF-β1 haplotype. [2327] The study by Peng et al .…”
Section: Introductionmentioning
confidence: 99%
“…[2327] The study by Peng et al . [23] suggested that C-509T and T869C gene polymorphisms in TGF-β1 might be a critical risk factor for genetic susceptibility to confidence interval (CI) and the study by Tao et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation